Implementasi Pemikiran Konstruktivisme dalam Pendidikan Agama Islam Kontemporer Abad Ke-21: Penelitian - Nok Uzana; Abdul Khobir (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Islamic Religious Education (IRE) plays a strategic role in shaping the character, moral identity, and spirituality of students amid increasingly complex social dynamics and technological developments. Traditional learning models that focus on memorization and one-way information delivery are no longer considered adequate to meet the learning needs of the 21st century, which demands critical and creative thinking skills as well as the formation of reflective and meaningful understanding. This article aims to examine the implementation of the constructivism approach as an alternative learning model in the context of contemporary PAI. This study uses a qualitative descriptive method based on a literature review with content analysis techniques to identify the suitability of constructivism theory with the principles of Islamic pedagogy. The results show that constructivism is in line with the concept of Islamic education, which emphasizes the stages of reflective thinking through tadabbur, tafakkur, and ijtihad. Constructivist-based learning models, such as Problem-Based Learning, Project-Based Learning, and experiential learning, have been proven to increase student engagement, strengthen conceptual understanding, and build the internalization of Islamic values in a contextual manner. Thus, the constructivist approach provides a strategic opportunity to realize PAI learning that is humanistic, dialogical, and relevant to the challenges of the modern era, without losing the theological essence and spirituality of Islam.